2002
DOI: 10.1002/ppp.416
|View full text |Cite
|
Sign up to set email alerts
|

Palaeoclimate reconstruction on Big Lyakhovsky Island, north Siberia—hydrogen and oxygen isotopes in ice wedges

Abstract: Late Quaternary permafrost deposits on Big Lyakhovsky Island (New Siberian Islands, Russian Arctic) were studied with the aim of reconstructing the palaeoclimatic and palaeoenvironmental conditions of northern Siberia. Hydrogen and oxygen stable isotope analyses are presented for six different generations of ice wedges as well as for recent ice wedges and precipitation. An age of about 200 ka BP was determined for an autochtonous peat layer in ice‐rich deposits by U/Th method, containing the oldest ice wedges … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
235
2
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 169 publications
(264 citation statements)
references
References 22 publications
24
235
2
3
Order By: Relevance
“…It reached the lowest values at the end of the LGM (17-16 ka) and sharply rose to probably the highest values between 15 and 12 ka. Winter temperature during the interval from ca 50 to 12 ka was constantly much lower than present, as evidenced by continuous growth of thick ice wedges and the stable isotope composition of ice (Meyer et al, 2002). Even during pre-LGM time (Middle Weichselian), the reconstructed winter temperature was at least 7 1C lower than today (Meyer et al, in prep.).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It reached the lowest values at the end of the LGM (17-16 ka) and sharply rose to probably the highest values between 15 and 12 ka. Winter temperature during the interval from ca 50 to 12 ka was constantly much lower than present, as evidenced by continuous growth of thick ice wedges and the stable isotope composition of ice (Meyer et al, 2002). Even during pre-LGM time (Middle Weichselian), the reconstructed winter temperature was at least 7 1C lower than today (Meyer et al, in prep.).…”
Section: Discussionmentioning
confidence: 99%
“…Our recent work at the site was explicated with great detail in a series of reports (Siegert et al, 1999a, b;Sher et al, 2000Sher et al, , 2002b, presenting the geomorphology of the site, field descriptions of the section, lithology, permafrost features, sampling areas, and complete lists of various samples. These data, along with the results of age determinations, analysis of sedimentology, stable isotopes of ice wedges, the preliminary studies of organic fossils (pollen, plant macrofossils, testate amoebae, insects and mammals) were summarized in recent publications (Andreev et al, 2002;Meyer et al, 2002;Schirrmeister et al, 2002a, b;Siegert et al, 2002).…”
Section: The Study Sitementioning
confidence: 99%
“…Therefore, samples taken from the top of ice wedges or from the bottom of the sediment column above ice wedges must be interpreted with caution for paleoclimatic purposes. The lateral influence between ice wedge and sediment has been demonstrated before (Meyer et al, 2002a). In the Barrow permafrost tunnel, the first two or three ice wedge samples adjacent to the lateral contacts (A, E, C 0 ) show a heavier isotopic composition than other samples of stable isotope cluster 1 (Fig.…”
Section: Winter Precipitation and Genetic Implications For The Buriedmentioning
confidence: 99%
“…Michel (1990) found that wedge ice may bear little relationship to that of the surrounding sediment due to the different geneses of wedge ice and texture ice. Isotopic and also ionic exchange is presumably driven by moisture migration of bound water (Meyer et al, 2002a), which tends to compensate potential differences either in ion concentration or temperature (Yershov, 1998). Therefore, these samples were discarded from paleoclimatic interpretation and the first accepted sample was at 30 cm distance from the lateral contacts.…”
Section: Winter Precipitation and Genetic Implications For The Buriedmentioning
confidence: 99%
“…Considering that ice wedges account for about 50% by volume of most Yedoma sequences, the total volumetric ground ice content likely ranges from 65 to 90%. Meyer et al, 2002;Vasil'chuk, 1992;Wetterich et al, 2011).…”
Section: Cryolithologymentioning
confidence: 99%